Biologiczne znaczenie chromu III dla organizmu człowieka - Piotrowska, Anna; Pilch, Wanda; Tota, Łukasz; Nowak, Gabriel (Medycyna pracy, 2018)
Currently, chromium is probably the most controversial transition metal. In recent publications it is clearly stated that it is not an essential micronutrient and should be considered to have a pharmacological effect. Conflicting scientific reports along with a huge amount of dietary supplements, as well as dietary and sports nutrients available on the market have prompted the authors to investigate the available information on the range of possible application, efficacy and safety of products containing salts or chelates of chromium III. The authors reviewed articles in electronic databases for the years 1959-2016, and selected works describing the biochemical, physiological and toxic properties of chromium salts and chelates and the range of possible applications in medicine, dietetics and sport. A critical analysis of reports dealing with the effect of chromium on the carbohydrate and lipid metabolism, body composition, lean body mass and sports performance was carried out. The authors indicated papers analyzing the mechanism of action of chromium in the cognitive and affective disorders. Much attention has been paid to the safety use of chromium III supplements. There are still some unsolved issues. In the field of toxicology, a limited number of reports about environmental exposure to trivalent chromium in the workplace draws our attention. In the field of biochemical research, there is still a need to clarify the mechanism of psychiatric and endocrinological activity, especially in conjunction with the immune system. Med Pr 2018;69(2):211-223.
Keywords: stopové prvky; potravní doplňky; sloučeniny chromu; Carbohydrate Metabolism; Chromium Compounds; Trace Elements; metabolismus lipidů; lidé; metabolismus sacharidů; Chromium; chrom; Lipid Metabolism; Humans; Dietary Supplements